2000
DOI: 10.1103/physrevstab.3.071301
|View full text |Cite
|
Sign up to set email alerts
|

Particle dynamics in multistage wakefield collider

Abstract: The dynamics of particles in laser pulse-driven wakefields over multistages in a collider is studied. A map of phase space dynamics over a stage of wakefield acceleration induced by a laser pulse (or electron beam) is derived. The entire system of a collider is generated with a product of multiple maps of wakefields, drifts, magnets, etc. This systems map may include offsets of various elements of the accelerator, representing noise and errors arising from the operation of such a complex device. We find that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 18 publications
2
45
0
Order By: Relevance
“…Computer simulation indicates that when the acceleration phase is approximately fixed (the phase slip is small) there is an inverse power behavior (for a fixed final energy of the particles), in particular, the emittance degradation decreases like l/N T , where NT is the total number of acceleration units. This confirms the theoretical expectation of CTHY deduced from a statistical theory [5]. The inverse power law suggested that through the use of small acceleration intervals one may be able to achieve high resilience against jitters.…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations
“…Computer simulation indicates that when the acceleration phase is approximately fixed (the phase slip is small) there is an inverse power behavior (for a fixed final energy of the particles), in particular, the emittance degradation decreases like l/N T , where NT is the total number of acceleration units. This confirms the theoretical expectation of CTHY deduced from a statistical theory [5]. The inverse power law suggested that through the use of small acceleration intervals one may be able to achieve high resilience against jitters.…”
Section: Introductionsupporting
confidence: 77%
“…To study such an accelerator system we introduced a map approach described in [3][4][5]. The longitudinal phase space transformations (for the differential phase 5W and the differential Lorenz factor $7 , respectively) stage by stage are described by the longitudinal map: <J* n+ i = **n (1) <$7 n+ i = 2 7 |$ 0 (cos(W s + A) -cos *,)<**" + 5 7n ,…”
Section: Multistage Acceleration Map Approach and Emittance Degradationmentioning
confidence: 99%
See 3 more Smart Citations